Plant Based Polyphenol Associations with Protein : A Prospective Review - Diana, Tazeddinova; Md. Rezaur, Rahman; Sinin, Hamdan; Mohammed Mahbubul, Matin; Muhammad Khusairy, Bakri; Mohammed M., Rahman (NC State University, 2022)
This review discusses the classes of plant polyphenols along with their binding mechanisms with protein molecules. Generally, polyphenols bind in covalent and non-covalent orientations with protein molecules. Their addition to the protein usually results in undesirable flavors and tastes inside the proteins. They also affect the color of the food. Plant polyphenols are found to act in a protective way against cardiovascular disease, neurodegenerative diseases, diabetes, and cancer. In addition to redox activity, their modes of action include the inhibition of key enzymes, modulation of transcription factors or cell receptors, and finally, perturbation of protein aggregates. Dietary polyphenols usually play a key role in protein digestion by forming covalent and non-covalent bonds with proteins. In addition, polyphenols and plant phenolics possess the scavenging ability of reactive oxygen species (ROS), including radical/non-radical oxygen species including HOC•, H2O2, HOCl, 1O2 (singlet oxygen), and oxidatively generated radicals derived from LDL biomolecules such as ROOC• and oligonucleic acids.